1996
DOI: 10.1007/bf03259133
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Moclobemide: An update of its pharmacological properties and therapeutic use

Abstract: The Editor regrets the omission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Moclobemide is a reversible and selective inhibitor of monoamine oxidase (MAO) A and was found to be e¤ective in the treatment of depression (Silverstone 1993;Fulton and BenÞeld 1996). In addition to being e¤ective in depressive disorders, studies have shown moclobemide to be e¤ective in anxiety disorders (Versiani et al 1992(Versiani et al , 1997Nutt and Montgomery 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Moclobemide is a reversible and selective inhibitor of monoamine oxidase (MAO) A and was found to be e¤ective in the treatment of depression (Silverstone 1993;Fulton and BenÞeld 1996). In addition to being e¤ective in depressive disorders, studies have shown moclobemide to be e¤ective in anxiety disorders (Versiani et al 1992(Versiani et al , 1997Nutt and Montgomery 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Moclobemide has an elimination half-life of 1.6-2.1 h in healthy volunteers [2,33,36,39], which does not increase with age or renal impairment. The half-life is prolonged in patients with hepatic cirrhosis [33], and prolonged with multiple doses.…”
Section: Figurementioning
confidence: 97%
“…Moclobemide is a reversible and selective inhibitor of monoamine oxidase (MAO) type A [1,2]. Controlled clinical trials have demonstrated it to be effective in the treatment of depressive disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a meta-analysis of the clinical trials of moclobemide, a reversible inhibitor of monaoamine oxidase-A (RIMA) indicated that it, too was superior to TCAs in bipolar depression (7). RIMAs, unlike nonreversible inhibitors of monoamine oxidase such as tranylcypromine, are less likely to interact with monoamine containing food stuffs to produce a hypertensive reaction (8) and dietary restrictions are generally not required.…”
Section: Introductionmentioning
confidence: 99%